Nerve Plexus Anatomy 101 - Swenson, Gabriel; James, Emily; Ozen, Merve; Matthees, Nicholas G. (Seminars in Interventional Radiology, 2025)
Nerve plexuses are complex networks of interwoven nerves in the peripheral nervous system. This article provides a comprehensive overview of the anatomy and function of the major nerve plexuses in the human body. The main spinal nerve plexuses—cervical, brachial, abdominal, lumbar, and sacral—are examined in detail, including their spinal origins, anatomical locations, and the areas they innervate. Understanding the intricate anatomy of nerve plexuses is essential for interventionalists, as it aids in the diagnosis and treatment of various neurological disorders affecting the peripheral nervous system.
Keywords: interventional radiology; nerve plexus; anatomy; neurolysis; nerve block